Validación del protocolo Five Dot Drill para medir coordinación y agilidad en jugadores de baloncesto entre los 10 y los 24 años de edad (2018)
The purpose of the research is the validation protocol FIVE DOT DRILL in basketball players between 10 and 24 years, it is to take three groups of 20 people by age, completing a total of 60 people, each group is applied DOT FIVE DRILL protocol implementing tool OPTO-GAIT later the Illinois Agility test, data collection to establish a relationship between different groups is carried out through normality tests were applied, which were concluded in respect abnormal the population quantity; the study shows correlations by age concerning the tests applied, however not establish anthropometric variables regarding the testing of Illinois or Test Protocol Five Dot Drill, although the relationship between test argues that the protocol can be used to estimate agility in basketball.